Efficacy of low-dose spironolactone on top of angiotensin receptor blockade in patients with glomerulonephritis - Byung Chul Yu; Min Sung Lee; Jong Joo Moon; Soo Jeong Choi; Jin Kuk Kim; Seung Duk Hwang; Moo Yong Park (The Korean Society of Nephrology, 2018)
Background: Previous studies have shown that aldosterone antagonists have a proteinuria-lowering effect in patients with proteinuria and progressive proteinuric disease not adequately controlled by the use of angiotensin receptor blockers (ARBs). Aldosterone antagonists, in combination with ARBs, might improve proteinuria in patients with glomerulonephritis (GN). Methods: In the present retrospective study, we evaluated the proteinuria-lowering effect and drug safety of low-dose spironolactone (12.5 mg/day) in 42 patients with GN being treated with an ARB. Results: Proteinuria decreased from a mean total-protein-to-creatinine (TP/Cr) ratio of 592.3 ± 42.0 mg/g at baseline to 335.6 ± 43.3 mg/g after three months of treatment with spironolactone (P⟨ 0.001). After the initial three months, the mean TP/Cr ratio increased progressively at six, nine, and 12 months; however, it was still less than the baseline value (P = 0.001, < 0.001, and < 0.001, respectively). Although serum Cr levels increased significantly at three and nine months compared with baseline (P = 0.036 and 0.026, respectively), there was no time effect of treatment (P = 0.071). Serum potassium levels tended to increase with time (P = 0.118), whereas systolic and diastolic blood pressures decreased with time (P = 0.122 and 0.044, respectively). Conclusion: Low-dose spironolactone in combination with an ARB reduced proteinuria in patients with GN, which could represent a novel treatment option in individuals whose proteinuria is not optimally controlled by the use of ARBs alone.